2011
DOI: 10.1128/jcm.02326-10
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinofacial Mucormycosis Caused by Mucor irregularis (Rhizomucor variabilis) in India

Abstract: In this article, we describe a chronic case of rhinofacial mucormycosis caused by Mucor irregularis, formerly known as Rhizomucor variabilis var. variabilis, a rare mycotic agent in humans. The infection caused progressive destruction of the nasal septum and soft and hard palate, leading to collapse of the nose bridge and an ulcerative gaping hole. The mucoralean mold cultured from a nasal biopsy specimen was determined by multilocus DNA sequence data to be conspecific with M. irregularis. CASE REPORTAn 18-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
41
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 19 publications
0
41
0
3
Order By: Relevance
“…Drogari-Apiranthitou et al (23) studied potential interactions between anidulafungin and amphotericin B against 21 mucormycetes and observed synergism against one Mucor circinelloides isolate and no antagonism. Further, synergism of caspofungin-amphotericin B and caspofungin-posaconazole combinations against M. irregularis isolates has been observed, according to a few case reports (7,8). Besides, previous research has shown that an echinocandin plus a polyene could markedly improve the survival of mice with diabetic ketoacidosis and disseminated mucormycosis (24,25).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Drogari-Apiranthitou et al (23) studied potential interactions between anidulafungin and amphotericin B against 21 mucormycetes and observed synergism against one Mucor circinelloides isolate and no antagonism. Further, synergism of caspofungin-amphotericin B and caspofungin-posaconazole combinations against M. irregularis isolates has been observed, according to a few case reports (7,8). Besides, previous research has shown that an echinocandin plus a polyene could markedly improve the survival of mice with diabetic ketoacidosis and disseminated mucormycosis (24,25).…”
mentioning
confidence: 98%
“…To our knowledge, with the exception of some reported cases (7,9), no susceptibility of M. irregularis to combinations of antifungal drugs in vitro has been reported. In the present study, the combinations of terbinafine or caspofungin with amphotericin B, posaconazole, or itraconazole were assessed against M. irregularis isolates in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This infer- ence is based on the fact that hyaline, coenocytic hyphae were detected by direct microscopy in the nasal crust specimen; this fungus was the only mold cultured from the patient's nasal cavity and grew well at 37°C and 40°C. Although rhino-orbitocerebral infections caused by mucoraceous molds are the most common mycoses among Indian patients (5, 6, 9), only about one-fifth are cultured and identified at the genus level (11), suggesting that novel etiologic agents are likely overlooked in India in the absence of detailed morphological and/or molecular phylogenetic data confirming the identification. Note that our data strongly suggest but do not confirm that T. lucknowense caused the infection, because no cultures were made using tissue samples from deep within the patient and an autopsy was not performed.…”
mentioning
confidence: 99%
“…Methods to obtain multilocus DNA sequence data, including extraction of total genomic DNA, PCR amplification, and DNA sequencing, followed published protocols (11,14,15). Briefly, isolate NRRL 54533, and the ex-type strains of Thamnostylum nigricans NRRL 6243, T. piriforme NRRL 2342, and T. lucknowense NRRL 2892 and the ex-neotype strain of T. repens NRRL 6241, were cultured in yeast-malt broth (0.3% yeast extract, 0.3% malt extract, 0.5% peptone, 2% dextrose; Difco, Detroit, MI) and then harvested over a Büchner funnel.…”
mentioning
confidence: 99%